Biological mechanisms and applied prospects of mesenchymal stem cells in premature ovarian failure. Issue 32 (12th August 2022) - Shi, Lan; Zhang, Zhifen; Deng, Miao; Zheng, Fangyuan; Liu, Wenhua; Ye, Shujin
Abstract : Premature ovarian failure (POF), also known as primary ovarian insufficiency (POI), refers to the loss of ovarian function in women after puberty and before the age of 40 characterized by high serum gonadotropins and low estrogen, irregular menstruation, amenorrhea, and decreased fertility. However, the specific pathogenesis of POF is unexplained, and there is no effective therapy for its damaged ovarian tissue structure and reduced reserve function. Mesenchymal stem cells (MSCs), with multidirectional differentiation potential and self-renewal ability, as well as the cytokines and exosomes they secrete, have been studied and tested to play an active therapeutic role in a variety of degenerative pathologies, and MSCs are the most widely used stem cells in regenerative medicine. MSCs can reverse POI and enhance ovarian reserve function through differentiation into granulosa cells (GCs), immune regulation, secretion of cytokines and other nutritional factors, reduction of GCs apoptosis, and promotion of GCs regeneration. Many studies have proved that MSCs may have a restorative effect on the structure and fertility of injured ovarian tissues and turn to be a useful clinical approach to the treatment of patients with POF in recent years. We intend to use MSCs-based therapy to completely reverse POI in the future.